Effect of the Masako maneuver and neuromuscular electrical stimulation on the improvement of swallowing function in patients with dysphagia caused by stroke - Byeon, Haewon (Journal of Physical Therapy Science, 2016)
[Purpose] The aim of this study was to compare improvements in swallowing function bythe intervention of the Masako maneuver and neuromuscular electrical stimulation inpatients with dysphagia caused by stroke. [Subjects and Methods] The Masako maneuver(n=23) and neuromuscular electrical stimulation (n=24) were conducted in 47 patients withdysphagia caused by stroke over a period of 4 weeks. Swallowing recovery was recordedusing the functional dysphagia scale based on videofluoroscopic studies. [Results] Meanfunctional dysphagia scale values for the Masako maneuver and neuromuscular electricalstimulation groups decreased after the treatments. However, the pre-post functionaldysphagia scale values showed no statistically significant differences between the groups.[Conclusion] The Masako maneuver and neuromuscular electrical stimulation each showedsignificant effects on the improvement of swallowing function for the patients withdysphagia caused by stroke, but no significant difference was observed between the twotreatment methods.